An Analysis of the Financial Performance of BUMDes in Enhancing Village Revenue: A Case Study of Rejoagung Village, Kedungwaru District, Tulungagung Regency. - Pratama, Rizki; Murdiyanto, Edi; Mahaputra, Agung Pambudi (Journal of Practical Management Studies, 2025)
This study aims to analyze the financial performance of RejoagungMakmur Village-Owned Enterprise (BUMDes) in Rejoagung Village, determine the contribution of BUMDes financial management to increasing village original income (PADes), and identify supporting and inhibiting factors in BUMDes financial performance. The method uses a quantitative approach with multiple linear regression analysis techniques. The financial ratios analyzed include profitability and operational efficiency. The calculation results show that RejoagungMakmurBUMDes has quite good financial performance. Partial tests show that liquidity has a significant effect on village original income with a significance value of 0.010 and a contribution of 42.0%. Profitability also has a significant effect with a significance value of 0.004 and a contribution of 42.7%. Operational efficiency has a significant effect with a significance value of 0.014 and a contribution of 58.8%. Furthermore, simultaneous tests show that the three variables together have a significant effect on PADes with a significance value of 0.000 and a contribution of 67.4%. This study provides strategic recommendations for strengthening BUMDes institutions and governance in a sustainable manner.